A Study on Parameter Optimization of the Delamination Factor (Fd) in Milling Kenaf Fiber Reinforced Plastics Composite Materials Using DOE Method / Azmi Harun...[et al.] - Harun, Azmi; Sia, Ting Ting; Che Haron, Che Hassan; A. Ghani, Jaharah; Mokhtar, Suhaily (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Kenaf is known by its scientific name, Hibiscus cannabinus, which is similar to jute and cotton, and is also a warm-season annual fibrous crop. In the past, it was used to make sackcloth, and its twine was used to manufacture rope. Kenaf is also used as a cordage crop. A machine’s surface quality normally depends for its reliability in the service application. The machining process changes the mechanical and chemical properties of individual constituents used for the composite. The objectives of this research are to study the effects of milling parameters and to determine the optimum conditions for a range of milling parameters to minimize the delamination factor (Fd) in milling kenaf fiber-reinforced plastic composite using the Taguchi Method. The Taguchi Method L8 (23) design was used to conduct a non-sequential experiment. The experimental results were analyzed using the Minitab 16 software. A study was carried out to investigate the relationship between the milling parameters, and their effects on the kenaf reinforced plastic. The composite panels were fabricated using the vacuum assisted resin transfer molding (VARTM) method. This study determined that the optimum parameters for the minimum delamination factor were a cutting speed of 16 Vm/min, a feed rate of 0.1 mm/tooth, and a depth of cut of 2.0 mm. The feed rate and cutting speed made the biggest contributions to the delamination factor (Fd). The use at high spindle speeds and low feed rates led to minimized delamination factor (Fd) during the milling of kenaf reinforced plastic composite materials.